PENGARUH MENTAL ACCOUNTING, HERDING BEHAVIOR DAN OVERCONFIDENCE TERHADAP KEPUTUSAN INVESTASI (STUDI KASUS PADA KANTOR PERWAKILAN BURSA EFEK INDONESIA BENGKULU) - Ummul Khair; Rebi Rahmad Ramadan; Rina Yuniarti; Nensi Yuniarti Zs (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to analyze the influence of mental accounting, herding behavior, and overconfidence on investment decisions among investors registered at the Bengkulu Representative Office of the Indonesia Stock Exchange (IDX). The research method used is quantitative research with primary data collection through the distribution of questionnaires to 100 respondents who are investors in Bengkulu. The results show that mental accounting has a negative effect on investment decisions, herding behavior has a positive effect, and overconfidence has a positive effect on investment decisions. The conclusion of this study states that mental accounting, herding behavior, and overconfidence significantly influence investment decisions among investors in the city of Bengkulu. Keywords: Mental accounting, Herding behavior, Overconfidence, Investment decisions, Indonesia Stock Exchange